2016
DOI: 10.1002/cbf.3162
|View full text |Cite
|
Sign up to set email alerts
|

Direct action of capsaicin in brown adipogenesis and activation of brown adipocytes

Abstract: The ingestion of capsaicin, the principle pungent component of red and chili peppers, induces thermogenesis, in part, through the activation of brown adipocytes expressing genes related to mitochondrial biogenesis and uncoupling such as peroxisome proliferator-activated receptor (Ppar) γ coactivator-1α (Pgc-1α) and uncoupling protein 1 (Ucp1). Capsaicin has been suggested to induce the activation of brown adipocytes, which is mediated by the stimulation of sympathetic nerves. However, capsaicin may directly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 51 publications
0
49
1
4
Order By: Relevance
“…13) TRPV1 is expressed in brown adipocytes, [55][56][57] and adipocyte cell lines such as the HB2 brown adipocyte cell line and the 3T3-L1 adipocyte cell line. 55) In 3T3-L1 cells, activation of TRPV1 by capsaicin induces calcium influx and prevents adipogenesis.…”
Section: Role Of Thermo-sensitive Trp Channels In Adipose Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…13) TRPV1 is expressed in brown adipocytes, [55][56][57] and adipocyte cell lines such as the HB2 brown adipocyte cell line and the 3T3-L1 adipocyte cell line. 55) In 3T3-L1 cells, activation of TRPV1 by capsaicin induces calcium influx and prevents adipogenesis.…”
Section: Role Of Thermo-sensitive Trp Channels In Adipose Tissuementioning
confidence: 99%
“…13) TRPV1 is expressed in brown adipocytes, [55][56][57] and adipocyte cell lines such as the HB2 brown adipocyte cell line and the 3T3-L1 adipocyte cell line. 55) In 3T3-L1 cells, activation of TRPV1 by capsaicin induces calcium influx and prevents adipogenesis. 58) Opposite results were also reported and showed that treatment with capsaicin in the late stage slightly increased expression levels of fatty acid-binding protein 4 (Fabp4), Pparγ2, and peroxisome proliferator-activated receptor γ coactivator-1α (Pgc-1α) in the HB2 brown adipocyte cell line.…”
Section: Role Of Thermo-sensitive Trp Channels In Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Administration of capsaicin in mice has shown to induce thermogenesis via the activation of BAT [88]. This is evidenced by the increase in markers related to mitochondrial biogenesis such as PPARγ, PGC-1α and UCP1 [88].…”
Section: Phytochemicals In Obesitymentioning
confidence: 99%
“…This is evidenced by the increase in markers related to mitochondrial biogenesis such as PPARγ, PGC-1α and UCP1 [88]. Capsaicin also induces the development of beige adipocytes at an early stage of adipogenesis [88].…”
Section: Phytochemicals In Obesitymentioning
confidence: 99%